A National Review of Insurance Coverage of Noncancerous Breast Reconstruction. Issue 3 (September 2021) - Klein, Marissa; Ha, Michael; Yang, Annie; Ngaage, Ledibabari M.; Slezak, Sheri; Rasko, Yvonne
Abstract : Background: Breast reconstruction is commonly performed for a multitude of noncancerous indications, such as correction of congenital deformities, acquired tissue disease, burns, and trauma. However, breast reconstruction for noncancerous indications is often considered cosmetic or not explicitly mentioned in insurance policies. The goal of this study was to assess variability in insurance coverage of breast reconstruction for noncancerous indications. Methods: The authors conducted a cross-sectional analysis of 102 US insurance companies, including Medicare and Medicaid, for coverage of breast reconstruction for noncancerous indications (Poland syndrome, fibrocystic breast disease, burns and trauma). Insurance companies were selected based on their state enrollment data and market share. A Web-based search and individual telephone interviews were conducted to identify the policy. Medical necessity criteria were abstracted from publicly available policies. Results: Half of the insurers (49%, n = 50) had no policy for Poland syndrome, 46% (n = 47) had no policy for burns and trauma, and 82% (n = 84) had no policy for fibrocystic breast disease. Fifty-two percent (n = 22) of policies providing coverage for Poland syndrome, 24% (n = 13) of policies providing coverage for burns and trauma, and 58% (n = 7) of policies providing coverage for fibrocystic breast disease had specific, stringent criteria for medical necessity. Thirty-six percent (n = 15) of policies covering Poland syndrome, 47% (n = 26) of policies covering burns and trauma, and 33% (n = 4) of policies covering fibrocystic breast disease include coverage of the contralateral breast. Conclusions: There is a paucity of publicly available information on insurance coverage of breast reconstruction for noncancerous indications and a lack of consensus between top US insurance companies on what constitutes medical necessity for surgical correction.